2023
DOI: 10.1097/bpo.0000000000002469
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Pediatric Orthopedic Surgery Care During the COVID-19 Pandemic Pre-vaccine and Post-Vaccine Availability

Abstract: Background: The COVID-19 pandemic has led to significant disruptions in medical care, resulting in an estimated 40% of US adults avoiding care. However, the return to baseline health care utilization following COVID-19 restrictions within the pediatric orthopedic population remains unexplored. We sought to analyze the visit volume and demographics of pediatric orthopedic patients at 3 timepoints: prepandemic (2019), pandemic (2020), and pandemic post-vaccine availability (2021), to determine the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The years after 2020 were not considered in our study, but the literature shows interesting results for this period. For example, a trend towards decreased injuries persisted for 12 months after the peak of the pandemic [ 5 ], and the number of paediatric orthopaedic surgery visits did not return to prepandemic levels in 2021 [ 6 ]. In contrast, a study by Kalem et al [ 35 ] found that after the first 3 months following the lockdown, the prevalence of outdoor traumas, high-energy traumas, the rate of patients treated with surgery, and the rate of admission to the emergency department were significantly higher than in the previous year.…”
Section: Resultsmentioning
confidence: 99%
“…The years after 2020 were not considered in our study, but the literature shows interesting results for this period. For example, a trend towards decreased injuries persisted for 12 months after the peak of the pandemic [ 5 ], and the number of paediatric orthopaedic surgery visits did not return to prepandemic levels in 2021 [ 6 ]. In contrast, a study by Kalem et al [ 35 ] found that after the first 3 months following the lockdown, the prevalence of outdoor traumas, high-energy traumas, the rate of patients treated with surgery, and the rate of admission to the emergency department were significantly higher than in the previous year.…”
Section: Resultsmentioning
confidence: 99%